Analisis Penerapan Strategi Pemasaran Kerupuk Amplang Ikan Bandeng Kelompok Wanita Pesisir Desa Saliki Kecamatan Muara Badak - Hasbiah, Hasbiah; ILHAM, ILHAM; WIJAYANTI, SILVANA KARDINAR (SEKOLAH TINGGI ILMU EKONOMI TENGGARONG, 2021)
SME has been proven playing important role in Indonesia economy. Wanita Pesisir is one of women’s groups that produce milkfish amplang cracker located in Muara Badak District, Kutai Kartanegara, East Borneo. The purpose of this sudy is to determine the internal strengths and weaknesses and external opportunities and threats of the business in purpose of developing appropriate development strategies. Through a focus group discussion with the members of Wanita Pesisir group, data collected then analyzed using SWOT Analysis. The result of this study revealed that then current position of Wanita Pesisir’s business is in Quadrant I meaning that the appropriate strategy for this business is growth/aggressive strategy.Keywords: SWOT Analysis, milkfish amplang cracker.